2003
DOI: 10.1078/0944-5013-00208
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of potentially pathogenic micro-organisms in Penaeus monodon larvae rearing systems in India

Abstract: Monodon baculovirls (MBV), external fouling organisms (EFO) and bacteria (especially Vibrio species) were monitored during 1996-1997 at nine different Penaeus monodon rearing hatcheries in India. Total cultivable heterotrophic bacteria, Vibrio-like-bacteria, presumptive Vibrio harveyi, Vibrio anguillarum, Vibrio vulnificus counts were determined from shrimp eggs, post larvae, rearing tank water, source sea water, feed (Artemia nauplii and microencapsulated feed). The MBV infected post larvae and their environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 20 publications
2
42
1
1
Order By: Relevance
“…The observation suggests that the occurrence of luminescent bacteria during nauplii stage in the rearing tank water could be an indicator of impending luminescent bacterial disease outbreak in the larval rearing tanks and possibly help in the prognosis of LBD. Although earlier studies reported the occurrence of luminescent bacterium in Artemia and Artemia hatching water (Abraham and Palaniappan, 2004;Vaseeharan and Ramasamy, 2003) we could not recover any luminescent bacteria from these samples. Similarly, the algal cultures did not contribute luminescent bacteria to the larval rearing tanks as reported by Lavilla-Pitogo et al (1992).…”
Section: Discussioncontrasting
confidence: 42%
“…The observation suggests that the occurrence of luminescent bacteria during nauplii stage in the rearing tank water could be an indicator of impending luminescent bacterial disease outbreak in the larval rearing tanks and possibly help in the prognosis of LBD. Although earlier studies reported the occurrence of luminescent bacterium in Artemia and Artemia hatching water (Abraham and Palaniappan, 2004;Vaseeharan and Ramasamy, 2003) we could not recover any luminescent bacteria from these samples. Similarly, the algal cultures did not contribute luminescent bacteria to the larval rearing tanks as reported by Lavilla-Pitogo et al (1992).…”
Section: Discussioncontrasting
confidence: 42%
“…Bacteria are known to be associated with endemic and epidemic diseases of shrimp (Lightner, 1996). However, microbial disease outbreaks occur at all stages of shrimps and are responsible for considerable economic losses in several countries (Vaseeharan, 2003). Opportunistic shrimp pathogenic bacteria are common in sea water, and will take advantage of ecological changes introduced when the water is used in aquaculture (Moriarty, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio parahaemolyticus are regularly linked to human food borne infections caused by consumption of undercooked or recontaminated shellfish [30]. Vibrio parahaemolyticus is an organism of concern in shrimp culture because some strains are associated with diseases in shrimp [55][56] and also because strains of this species are human pathogens, causing gastroenteritis [53,[57][58] worldwide and sporadic cases of and outbreaks occur regularly in Asia as well as in other countries [59]. It has also been reported in wound infection and in septicemia [60][61][62].…”
Section: Discussionmentioning
confidence: 99%